Analisis Penentuan Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Untuk Penetapan Harga Jual Pada UMKM Cone Ice Cream - Wardani, Alya; Prana, Riandani Rezki (CIVITAS: Jurnal Studi Manajemen, 2021)
The purpose of this research are to analyze the calculation of the cost of production of Cone Ice Cream carried out at Mrs. Narti's Cone Ice Cream UMKM, to analyze the cost of goods manufactured using the full costing method on Mrs. Narti's Cone Ice Cream, and to analyze the difference between the full costing method and the the method used by Mrs. Narti's Cone Ice Cream and its effect on the selling price. The data used in this study are primary data and secondary data. Primary data is taken by conducting direct interviews with UMKM owners and production employees who worked at Mrs. Narti's UMKM Cone Ice Cream, while secondary data was obtained through related books, other references in accordance with the research title and research results. Then the type of data used is descriptive qualitative data with data analysis carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the data analysis show that the calculation of the cost of goods manufactured by Mrs. Narti's Cone Ice Cream is Rp. 2,435, - while the result of the analysis of the calculation of the cost of production using the full costing method is Rp. 2,580, - so the difference between the full costing method and the one done the company is Rp. 145, -, and the selling price based on the calculation of the full costing method is Rp. 3,417. So the most appropriate method is the full costing method because this method will take into account all costs incurred during the production process.